Review of Supreme Court Regulation Number 5 of 2019 on The Consideration of The Judge Rejecting Dispensation of Pregnant Marriage (Analysis of Decision Number 85/Pdt.P/2023/PA.Pn) - Ramadhani, Muhammad; Mariani, Mariani (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This study is motivated by the rejection of a request for dispensation of marriage by the judge of the Painan Religious Court with the condition that the child who applied for dispensation of marriage was pregnant outside of marriage due to her intimate relationship with her prospective husband. The judge's consideration rejected the application because the applicant’s child and husband candidate were not ready for marriage and free sexual behavior was increasingly rampant. This case is a dilemma considering the emergency situation of the pregnant the applicant’s child, where the judge is faced with two potential harms in granting or rejecting the petition. The purpose of this study is to determine the legal basis for the judge's consideration in rejecting the application for dispensation to marry the case and to find out the review of Supreme Court Regulation Number 5 of 2019 on Guidelines for Adjudicating Marriage Dispensation Applications against the judge's consideration. This type of research is normative legal research with a case approach. The collection of legal materials is done through document studies and literature studies. The results showed that the legal basis for the judge's consideration was Supreme Court Regulation Number 5 of 2019 as a guide in adjudicating cases, surah at-Tahrim verse 6, hadith about the recommendation to marry for those who are able, the opinion of scholars about the prohibition of marriage of pregnant women, Article 80 paragraph (2) of the Compilation of Islamic Law, and fiqh rules on rejecting harm in assessing the readiness of parties to marry. Based on the review of Supreme Court Regulation Number 5 of 2019 and the judge's consideration that the judge was not too sharp in digging up information, assessing the feasibility of the parties, and considering the social and psychological impact on the the applicant’s child and the fetus that is being conceived so that the protection and best interests of the child are not maximally implemented, the judge's rejection of this marriage dispensation application as a form of legal certainty by the judge to provide legal order for the phenomenon of free sex that is rampant in society. Keywords: Supreme Court Regulation Number 5 of 2019, Judge’s Consideration, Marriage Dispensation Abstrak Penelitian ini dilatarbelakangi adanya penolakan permohonan dispensasi kawin oleh hakim pengadilan agama painan dengan kondisi anak yang dimohonkan dispensasi kawin tengah hamil diluar nikah akibat hubungan intimnya dengan calon suami. Pertimbangan hakim menolak permohonan karena Anak pemohon dan calon suami belum siap untuk menikah dan semakin merajalelanya perilaku seks bebas. Perkara ini bersifat dilematis mengingat keadaan darurat dari anak pemohon yang tengah hamil, dimana hakim dihadapkan dua potensi kemudaratan dalam mengabulkan atau menolak permohonan. Tujuan penelitian ini untuk mengetahui dasar hukum pertimbangan hakim dalam menolak permohonan dispensasi kawin perkara tersebut dan mengetahui tinjauan perma nomor 5 tahun 2019 tentang pedoman mengadili permohonan dispensasi kawin terhadap pertimbangan hakim tersebut. Jenis penelitian ini adalah penelitian hukum normatif dengan pendekatan kasus. Pengumpulan bahan hukum dilakukan melalui studi dokumen dan studi pustaka. Hasil penelitian menunjukan bahwa dasar hukum pertimbangan hakim adalah dengan perma nomor 5 tahun 2019 sebagai panduan dalam mengadili perkara, surah at-tahrim ayat 6, hadits tentang anjuran menikah bagi yang sudah mampu, pendapat ulama tentang haramnya perkawinan wanita hamil, pasal 80 ayat (2) kompilasi hukum islam, dan kaidah fikih tentang menolak kemudaratan dalam menilai kesiapan pihak untuk menikah. Berdasarkan tinjauan perma nomor 5 tahun 2019 terhadap pertimbangan hakim tersebut bahwa hakim tidak terlalu tajam dalam menggali informasi, menilai kelayakan para pihak, dan mempertimbangkan dampak sosial dan psikologis terhadap anak pemohon dan janin yang tengah dikandungnya sehingga perlindungan dan kepentingan terbaik bagi anak tidak terlaksana secara maksimal, penolakan hakim atas permohonan dispensasi kawin ini sebagai wujud kepastian hukum oleh hakim untuk memberikan ketertiban hukum atas fenomena seks bebas yang tengah merajalela di tengah masyarakat. Kata Kunci: Perma Nomor 5 Tahun 2019, Pertimbangan Hakim, Dispensasi Kawin